Modeling of DNA Single Stage Splicing Language via Yusof-Goode Approach: One String with Two Rules - Yuhani, Yusof; Lim, Wen Li; Mohammad Hassan, Mudaber (2015)
Splicing system plays a pivotal role in attempts to recombine sets of double-stranded DNA molecules when acted by restriction enzymes and ligase. Traditional method of finding the result of DNA recombination through experiment is both time and money consuming. Hence, finding the number of patterns of DNA single stage splicing language through formalism of splicing system is a way to optimize the searching process. From the biological perspective, it predicts the number of types of molecules that will exist in the system under existence of restriction enzymes and ligase. In this paper, some theorems, corollaries and examples that lead to the predictions of single stage splicing languages involving one pattern string and two rules are presented via Yusof-Goode approach.